“PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK LIFE CAREER RAINBOW SUPER PADA KEMATANGAN KARIR PESERTA DIDIK KELAS X SMK N 2 BANDAR LAMPUNG DI ERA REVOLUSI INDUSTRI 5.0” - rima-anti-puspita sari (Universitas Veteran Bangun Nusantara, 2026)
Career maturity is an essential ability that students need to effectively plan and determine their future career choices. Preliminary research on tenth-grade students at SMK Negeri 2 Bandar Lampung indicated that most students were at a moderate level of career maturity, highlighting the need for appropriate guidance services. This study aims to examine the effect of group guidance using the Life Career Rainbow technique on students’ career maturity. A quantitative approach with a pre-experimental method and a one group pretest–posttest design was employed. The sample consisted of 7 students selected through purposive sampling. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant improvement, with an Asymp. Sig. (2-tailed) value of 0.018 (<0.05). Thus, the technique is effective in improving students’ career maturity.